A escrita literária de Jessier Quirino como marca da cultura regional: uma abordagem léxico-semântica - Santos, Ellem Kyara Pessoa dos (2024)
This research aimed to elaborate a glossary with expressions typical of northeastern speech. The base corpus was the lexicon used by the poet and regionalist writer Jessier Quirino in his three literary works: Agruras da lata d'água (2016), Paisagem de Interior (2018) and Galos de Campina (2018). Performing a lexical-semantic analysis of Quirinian works is quite relevant, since the writer seeks to emphasize, in his literary writing, the regional-popular language. This language, in turn, is presented through numerous regionalisms, ranging from expressions, archaisms and neologisms. For the systematization of the glossary, we rely on the assumptions of the lexical sciences: Lexicology and Lexicography (ARAGON, 2004), (BARBOSA, 1993), (BORBA, 2002). In particular, we rely on the theoretical methodological framework of Pottier (1972), for the classification of the lexies in: simple, composed, complex and textual. We also used the assumptions of Dialectology (CARDOSO, 2016), Sociolinguistics (BAGNO, 2004), Ethnolinguism (COSERIU, 1987) and Semantics (CANÇADO, 2013) to assess whether the expressions were of current or regional use and whether these were archaisms or neological creations of the author. It is worth pointing out that the purpose of this research is justified by the need to develop more work in this way, that is, systematizing regional speech in dictionary works, thus the current generation and the future access and knowledge to the rich cultural linguistic collection that are regional speakers. In this bias, our thesis contributes to the appreciation of regional speakers, as well as proves their richness and vastness, so present in the Brazilian Northeast. Thus, we cooperate for the studies of the lexical sciences, as well as for the critical fortune of the work of Jessier Quirino.